Pengaruh Motivasi Belajar Guru Terhadap Keterampilan Membuat Bahan Ajar Berbasis Informasi Dan Teknologi Di SMP Negeri 139 Jakarta - Khoirul Umam; Tjipto Djuhartono; Puput Irfansyah (RELASI : JURNAL EKONOMI, 2019)
The purpose of this research activity is to measure and determine whether or not there is influence between motivation to study MS Power Point and Blog programs on teacher skills in making presentation slides and Blogs by using MS Power Point and Blog programs in information-based teacher teaching materials preparation training programs and technology at 139 Jakarta Public Middle School. The target to be achieved specifically in this research activity is the output of research carried out can be used as an indicator of decisions and policies for the Head of Jakarta SMP Negeri 139 in an effort to improve the competence of teachers in the schools they lead. The type of research carried out is quantitative descriptive using a statistical approach from the primary data obtained. The method used in the research activities at 139 Jakarta Public Middle School is through a survey using a questionnaire and literature review as a support in this study. The results showed that there was a very low influence between teacher learning motivation and the teacher's ability to make teaching materials as evidenced by the calculation of the correlation coefficient of 0.043 or 4.3% which could be interpreted as teachers' awareness to learn and master teaching skills using learning media Information and Technology based is very low.